2014
DOI: 10.1377/hlthaff.2013.1224
|View full text |Cite
|
Sign up to set email alerts
|

US Health Spending Trends By Age And Gender: Selected Years 2002–10

Abstract: This article presents estimates of personal health care spending by age and gender in selected years during the period 2002-10 and an analysis of the variation in spending among children, working-age adults, and the elderly. Our research found that in this period, aggregate spending on children's health care increased at the slowest rate. However, per capita spending for children grew more rapidly than that for working-age adults and the elderly. Per capita spending for the elderly remained about five times hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 6 publications
7
67
0
Order By: Relevance
“…11 The average total cost incurred after the staged operations over a 15-year period is lower compared with the staged procedures period but still substantial. HLHS patients are estimated to require more resources on average as expected, and so are male children which is in line with the pediatric healthcare literature on gender 15 and previous Fontan studies. 16 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…11 The average total cost incurred after the staged operations over a 15-year period is lower compared with the staged procedures period but still substantial. HLHS patients are estimated to require more resources on average as expected, and so are male children which is in line with the pediatric healthcare literature on gender 15 and previous Fontan studies. 16 …”
Section: Discussionsupporting
confidence: 83%
“…These conditions are not currently recognized as one of the most common noncardiac inpatient needs for this population, although a few previous studies [15][16][17][18] have reported worse dental caries experience and comorbidities in digestive system for children with heart disease. However, it is unclear from this study whether these admissions simply reflect more inpatient needs for this population on commonly seen conditions due to anesthesia concerns or that these children indeed had worse dental and digestive outcomes.…”
mentioning
confidence: 97%
“…1 Reducing the use of these services could prevent iatrogenic harm (eg, radiation exposure from imaging tests) 2 while decreasing unnecessary financial burden on families and the health care system. 3 -11 Improving the efficiency of pediatric care is an increasingly important policy goal given the rapid rise in pediatric health care expenditures 12 as well as the proliferation of alternative payment models such as pediatric accountable care organizations (ACOs), which incentivize providers to judiciously use resources and enhance the quality of care. 13 -18 Large-scale analyses of overuse can be facilitated by measures that directly assess low-value pediatric service use in insurance claims databases.…”
mentioning
confidence: 99%
“…Reinhardt (2003) found that population aged 65 and over was 3 times more that population aged 34-44 (14). Lassman et al (2014) drew the conclusion that medical expenses per capita in the elderly was 5 times more that the children group (15). Alemayehu (2004) adopted a lift table model, using cross sectional medical expenses and death data of every single individual enrolled, to construct a hypothetical current population longitudinal medical expenses data from birth to death.…”
Section: Introductionmentioning
confidence: 99%